Occupational lead exposure in printing presses: an analytical approach (2008)
Lead absorption poses a great threat to the health of workers in printing presses where commercial publishing is done. A case example is the commercial printing operations in Lagos, Nigeria. Since regular exposure to lead dusts could result in lead poisoning, complications that could cause death of victims, monitoring and controlling lead absorption of operators is essential for the maintenance of workers’ health and for the avoidance of the risk of incurring heavy losses due to litigation. The purpose of this paper is to model the process, rate, and quantity of lead absorption in operators of printing presses. Measurements of lead absorption are made and compared to standards in individuals for control purposes. Two approaches are used. The first shows the risk of being poisoned by lead. The second approach relates lead poisoning to the rates of intake of lead into the body and its elimination out of the body. This model viewed the absorption of lead as a cycle and applied the continuity equation to this cycle.